(untitled) - Nieuwoudt, Enid

Effect of genetic variants in genes encoding two nuclear receptors (PXR and CAR) on efavirenz levels and treatment outcome in South African HIV-infected females (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2014.